Recognition of Prior Learning in Higher Education: A Systematic Literature Review - Raciti, Maria; Tham, Aaron; Dale, Joshua (Journal of University Teaching and Learning Practice, 2024)
The aims of this research are to describe recent, global, empirical understandings of the recognition of prior learning (RPL) and to synthesise and extant knowledge in a way that assists stakeholders in uplifting the transitions to education, employment, or training. RPL matters are particularly important to current sector policy initiatives as reforms to the Australian government’s approach to widening participation in higher education have helped in the development of the 2021 National Microcredentials Framework to define, standardise and consolidate RPL for Australian citizens. Furthermore, the recent 2024 Australian Universities Accord Final Report highlights the importance of RPL to facilitate lifelong learning. A systematic review guided by the PRISMA and PICO frameworks identified 65 articles published between 2013-2023, that empirically examined RPL. Using manual thematic analysis, 17 core themes were organised into five meta-themes: 1) the benefits of RPL; 2) the challenges of RPL; 3) RPL processes; 4) institutional processes; and 5) national RPL policy. This article provides timely insights to shape the future RPL research agenda as well as RPL practice and policy in Australia and beyond.